Cost-Effectiveness of Coronary Artery Bypass Surgery Versus Medicine in Ischemic Cardiomyopathy: The STICH Randomized Clinical Trial. Issue 11 (15th March 2022) - Chew, Derek S.; Cowper, Patricia A.; Al-Khalidi, Hussein; Anstrom, Kevin J.; Daniels, Melanie R.; Davidson-Ray, Linda; Li, Yanhong; Michler, Robert E.; Panza, Julio A.; Piña, Ileana L.; Rouleau, Jean L.; Velazquez, Eric J.; et al.
Abstract : Background: The STICH Randomized Clinical Trial (Surgical Treatment for Ischemic Heart Failure) demonstrated that coronary artery bypass grafting (CABG) reduced all-cause mortality rates out to 10 years compared with medical therapy alone (MED) in patients with ischemic cardiomyopathy and reduced left ventricular function (ejection fraction ⩽35%). We examined the economic implications of these results. Methods: We used a decision-analytic patient-level simulation model to estimate the lifetime costs and benefits of CABG and MED using patient-level resource use and clinical data collected in the STICH trial. Patient-level costs were calculated by applying externally derived US cost weights to resource use counts during trial follow-up. A 3% discount rate was applied to both future costs and benefits. The primary outcome was the incremental cost-effectiveness ratio assessed from the US health care sector perspective. Results: For the CABG arm, we estimated 6.53 quality-adjusted life-years (95% CI, 5.70–7.53) and a lifetime cost of 140 059 (95% CI, 106 401 to 180 992). For the MED arm, the corresponding estimates were 5.52 (95% CI, 5.06–6.09) quality-adjusted life-years and 74 894 lifetime cost (95% CI, 58 372 to 93 541). The incremental cost-effectiveness ratio for CABG compared with MED was 63 989 per quality-adjusted life-year gained. At a societal willingness-to-pay threshold of 100 000 per quality-adjusted life-year gained, CABG was found to be economically favorable compared with MED in 87% of microsimulations. Conclusions: In the STICH trial, in patients with ischemic cardiomyopathy and reduced left ventricular function, CABG was economically attractive relative to MED at current benchmarks for value in the United States. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00023595.